Critical success factors in the implementation of ISO 9001 : 2008 quality management system in academic library - Gan, Sie Sie, 1987-; Abdul Hakim Mohammed; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2011